IMPLEMENTATION OF LEARNING-BASED GAME METHOD TO IMPROVE ELEMENTARY STUDENTS’ LEARNING ACTIVENESS - Yusnarita Zega; Wiyun Philipus Tangkin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Students’ learning activeness is crucial in the ongoing learning process. In fact, there are still students who do not have active in learning. Based on the observation, it was found that there were still students who did not have active in learning. Students never expressed opinions and questions, students were not enthusiastic, students played or talked with friends during the learning process, students hesitated to express opinions, students often got permission to leave class, and students did not contribute to group discussions. The solution to these problems is to apply the game method in learning. The aim is to explain that the application of the game method can increase the students’ activeness in learning during the learning process in the classroom. The method used is a descriptive qualitative method. The result is that the application of the game method can increase students’ learning activeness. It is marked by a change in the response showed by students in which students become enthusiastic while participating in learning, students actively ask and answer questions, and students are actively involved in discussions and some of them are in accordance with indicators of student’s learning activeness. Nevertheless, to obtain significant results, a teacher can apply this method repeatedly. As a Christian teacher, of course, the teacher must be able to use their abilities and intellect to see the problems that students are experiencing in class, then the teacher seeks the right solution based on Bible truth. The suggestion that can be given to teachers is to evaluate the problems of students’ learning activeness in order to be able to determine other methods that are more effective for the improvement of students’learning activeness.